A well-rounded school library extent of compliance to library standards in the collection and services of elite schools in science and the arts - Macasero, Joseph Percival B. (2003)
This study focused on the extent of compliance of elite high school libraries' collection and service to standards set by the Department of Education Culture and Sports and feedback based from their users. Elite schools' libraries studied are libraries of schools specializing in sciences and the arts in the Philippines, namely Philippine Science High School and Philippine High School for the Arts. The researcher aimed to determine if the school library of these schools have a well-rounded collection and services that caters to their user who are in a way special because of their intelligence and talents.